Vestibular rehabilitation with visual stimuli in peripheral vestibular disorders - Manso,Andréa (2016)
ABSTRACT INTRODUCTION: Visual stimuli can induce vestibular adaptation and recovery of body balance. OBJECTIVE: To verify the effect of visual stimuli by digital images on vestibular and body balance rehabilitation of peripheral vestibular disorders. METHODS: Clinical, randomized, prospective study. Forty patients aged between 23 and 63 years with chronic peripheral vestibular disorders underwent 12 sessions of rehabilitation with visual stimuli using digital video disk (DVD) (experimental group) or Cawthorne-Cooksey exercises (control group). The Dizziness Handicap Inventory (DHI), dizziness analog scale, and the sensitized Romberg static balance and one-leg stance tests were applied before and after the intervention. RESULTS: Before and after the intervention, there was no difference between the experimental and control groups (p > 0.005) regarding the findings of DHI, dizziness analog scale, and static balance tests. After the intervention, the experimental and control groups showed lower values (p < 0.05) in the DHI and the dizziness analog scale, and higher values (p < 0.05) in the static balance tests in some of the assessed conditions. CONCLUSION: The inclusion of visual stimuli by digital images on vestibular and body balance rehabilitation is effective in reducing dizziness and improving quality of life and postural control in individuals with peripheral vestibular disorders.